2014
DOI: 10.1002/ccd.25694
|View full text |Cite
|
Sign up to set email alerts
|

Post‐procedural hemodiafiltration in acute coronary syndrome patients with associated renal and cardiac dysfunction undergoing urgent and emergency coronary angiography

Abstract: Our pilot study suggests that, in ACS patients with severe renal and cardiac insufficiency, treatment with an aggressive prophylactic hemodiafiltration session after urgent or emergency coronary angiography seems to be associated with a relevant improvement in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Prophylactic RRT in 3 out of 5 studies was HD, 22 - 24 and the other 2 studies were hemofiltration. 25 , 26 Only 3 studies showed the association between decreasing 1-year mortality rate and prophylactic RRT. 24 - 26 While the study by Hsieh et al 23 showed no significant benefit of prophylactic RRT in 1-year mortality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prophylactic RRT in 3 out of 5 studies was HD, 22 - 24 and the other 2 studies were hemofiltration. 25 , 26 Only 3 studies showed the association between decreasing 1-year mortality rate and prophylactic RRT. 24 - 26 While the study by Hsieh et al 23 showed no significant benefit of prophylactic RRT in 1-year mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The volume of contrast media is one of the most important contributing factors for CA-AKI in patients with CKD. Marenzi et al 25 , 26 demonstrated significant renal outcomes and 1-year mortality benefits of prophylactic periprocedural hemofiltration in 2003 and 2015. The studies were conducted in advanced CKD patients (creatinine level >2 mg/dL 26 and estimated glomerular filtration rate ≤30 mL/min/1.73 m 2 ) 25 who were exposed to a high volume of contrast agent (mean contrast volume >200 mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations